Progressive Coil Penile Tourniquet Syndrome: Single Center Experience with 26 Cases at Department of Pediatric Urology at the Institute of Kidney Diseases MTI Hayatabad Peshawar - Sayed Ghafar Shah, Muhammad Kamran Khan, Ali Asad, Naqib Ullah, M Asif Khan, Irfan, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: This study was conducted to know the causes of penile tourniquet injury, its complications and awareness about the condition to prevent its devastating outcomes. Methods: this study was completed in five year (2017-2022) at Institute of Kidney Diseases MTI Hayatabad Peshawar. The injuries were graded ‘as described by Bashir and El-Barbary. Results: this study is composed of 26 Patients. . The mean age of patients was noted seven years (6.93years) with range 2.3years to 11years. Human hair was found constricting agent (09 patients). All of the patients were circumcised. In most patients a delay in diagnosis of more than five weeks was noted. Conclusion: Penile tourniquet injury in children can cause devastating range of injuries from mild glans edema to penile amputation. The knowledge of such conditions/injuries can easily diagnose the condition and prevent its complications.